Preparation and characterization of a new Schiff base N2O2 and its metal complexes with some divalent metal ions (Journal of the College of Basic Education, 2022)
The study included the preparation of a new tetra-chelated lipid base, N2O2, which was prepared from the reaction of the compound 3-(3-Phenylallylidene)pentane-2,4-dione with semicarbazide. Ni, Cu, Zn dual positive charge. The new compounds prepared were characterized by proton and carbon magnetic resonance spectroscopy and mass spectrometry, in addition to infrared spectroscopy, visible ultraviolet spectroscopy, microelemental analysis, and measuring the magnetic sensitivity of the prepared complexes. The results of molar conductivity also showed that the prepared complexes do not have the ionic character. From all of the above, the octahedral stereoscopic shapes of the prepared chylite complexes were proposed.